2021
DOI: 10.1007/s10943-021-01336-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between International Students’ Health Perceptions and Their Healthy Lifestyle Behaviors

Abstract: This study was carried out to examine the relationship between international students' health perceptions and their healthy lifestyle behaviors. This descriptive and relational study was conducted with 216 international students studying at a university in Turkey. Study data were collected using the descriptive information form, the Perception of Health Scale (PHS) and the Health-Promoting Lifestyle Profile II (HPLP-II). Data were evaluated using descriptive statistics and Pearson correlation analysis. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…However, around the globe, the young generation shows a low tendency toward participating in health promotion activities, as they believe that they are in a healthy stage of life (Al-Qahtani, 2019). Therefore, it is very important to improve the perception of health in young people to have them acquire healthy lifestyle behaviors (Citak Tunc et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, around the globe, the young generation shows a low tendency toward participating in health promotion activities, as they believe that they are in a healthy stage of life (Al-Qahtani, 2019). Therefore, it is very important to improve the perception of health in young people to have them acquire healthy lifestyle behaviors (Citak Tunc et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study with a nationwide U.S. sample indicated that spiritual individuals were significantly more likely to engage in higher levels of exercise because of the belief that one's body is a temple of God (Krause et al, 2017). In another study involving international undergraduate students in the Middle East, Tunc et al (2021) observed a positive link between students' spirituality and physical activity. The authors suggested that spiritual growth drives students' life goals, often including positive physical health behaviors such as exercise and sports.…”
Section: Spirituality and Exercisementioning
confidence: 99%